PELATIHAN SOFTWARE AKUNTANSI ACCURATE BAGI SISWA/I SMA KRISTEN YUSUF - Verawati Verawati; Silvia Chandrawati Susoni Basri; Benny Purnama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The accounting process studied in educational units is an accounting process that is carried out manually. Although learning it manually is important, existing technology can help in simplifying the accounting process. Many accounting software are available and can be selected for used in the company. One of the accounting software that is suitable for companies in Indonesia is Accurate software, because it has been adjusted to the Financial Accounting Standards that applicable in Indonesia and has been adjusted to the tax provisions in Indonesia. Knowledge of accounting software is important for students of SMA Kristen Yusuf because it can strengthen their skills in the accounting field. In addition, it can open their eyes that basic skills in operating information technology devices are very necessary, both for students who will continue their studies in higher education and for students who will directly enter the world or the world of work. The Accurate accounting software training activity for class XII students of SMA Kristen Yusuf was carried out by the PKM team in November 2021 using Zoom. The activity was held in 2 sessions and each training session was 90 minutes. The training implementation includes pre-test, material delivery, quiz during training, question and answer, and post-test. The output of this training activity is mandatory output in the form of articles in proceedings or journals. An additional output from this activity is a training module that has an ISBN.